Edukasi Pengelolaan Sampah Organik untuk Generasi Muda di SMPN 1 Kuningan - Hamdan, Hamdan; Made , I; Sri , Putu; Crisna , Gede (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Penatahan Village is a village located in Penebel sub-district, Tabanan regency, Bali Province. The Penatahan village has six hamlets consisting of Penatahan Kaja Hamlet, Penatahan Kelod Village, Mogan Hamlet, Bedugul Hamlet, Tegayang Hamlet, and Kekeran Hamlet. In Penatahan Village there is a unit education which includes Penatah 1 Public Elementary School and Kuningan 1 Public Junior High School which are located on Jl. Batukaru, Penatahan Village, Kec. Kuningan, Kab. Kiuningan. Penatahan village has natural attractions and attractions that can be used as tourist attractions, both natural, cultural, culinary, and spiritual attractions. Some of the attractions of Penatahan Village are natural hot springs which are the main attraction in Penatahan Village. The attractiveness of the Penatah village needs to be maintained and especially in the cleanliness of the surrounding environment. Behind all this, there are many efforts that must be made by the local government to be able to maintain quality in terms of adequate cleanliness and support this. In this case, the young generation plays an important role in participating. as well as maintaining the cleanliness of the surrounding environment, especially in the area that is most highlighted, namely the tourist area. The involvement of the younger generation in the Penatahan village is very important in efforts to maintain cleanliness because this is a shared responsibility in maintaining the cleanliness of the surrounding environment. The efforts that need to be made by the government local community, namely involving youth and adolescents in activities related to environmental hygiene and the need for education for youth and the younger generation so that this can be easily carried out in the future